SYMBOL OF WESTERN NEO-ORIENTALISM CRITICISM IN “MS. MARVEL” - Robingah, Robingah; Firstiyanti, Aulia Haris; Ilafi, Afiliasi; Suyudi, Suyudi; Sari, Mulya (Journal of Language and Literature, 2023)
The aim of this article is to construct a critique of Western neo-orientalism through the film medium.  Film is a product of popular culture.  After 9/11, the concept of neo-orientalism emerged in the West, especially in America, which considers everything that is not "Western" to be terrorists, and radicals.  To criticize the concept of neo-orientalism in “Ms.  Marvel” the researchers used the theory of identity from Stuart Hall and Homi Bhabha to get the concept of identity in this series. The concept of identity found is a construction of a critique symbol of Western neo-orientalism. The source of data in this research was a television miniseries entitled “Ms. Marvel” which live on Disney+.  The results of the analysis showed that there are Islamic symbols that appear in this series which are a construction of criticism of the concept of Western neo-orientalism. It can be implied from the result that "Ms.Marvel" is one of the examples of a construction of Neo-Orientalism criticism through the medium of Popular Culture.